2014
DOI: 10.1177/1358863x14550543
|View full text |Cite
|
Sign up to set email alerts
|

Quality of care among patients undergoing lower extremity revascularization

Abstract: Background: Compliance with guidelines for treating patients with peripheral artery disease (PAD) lags compliance for treating patients with coronary artery disease. We assessed the gap between guidelines and practice for patients with PAD who underwent lower extremity revascularization (LER) at our institution from 2007 to 2010. Methods: Quality of care (QoC) was calculated by measuring provider performance on four indicators (antiplatelet therapy, dyslipidemia management, control of hypertension, and diabete… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 37 publications
0
5
0
Order By: Relevance
“…Previous studies evaluating the impact of heart failure on short-term mortality and limb outcomes in CLI patients have demonstrated that heart failure is associated with increased mortality. 13,17,[30][31][32][33] However, mortality data extending beyond 1-year post-intervention is scarce and many have focused only on reduced ejection fraction as a risk factor for increased mortality. 11,14,15 The study by Meltzer and colleagues is the only other to our knowledge that directly compared the outcomes of PAD patients with heart failure based on ejection fraction.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies evaluating the impact of heart failure on short-term mortality and limb outcomes in CLI patients have demonstrated that heart failure is associated with increased mortality. 13,17,[30][31][32][33] However, mortality data extending beyond 1-year post-intervention is scarce and many have focused only on reduced ejection fraction as a risk factor for increased mortality. 11,14,15 The study by Meltzer and colleagues is the only other to our knowledge that directly compared the outcomes of PAD patients with heart failure based on ejection fraction.…”
Section: Discussionmentioning
confidence: 99%
“…Among patients with claudication or CLI undergoing lower extremity revascularization, Slovut et al recently reported a 48% rate of ACEI use at both admission and discharge. 43 In a study analyzing data from a general PAD population, Pande et al 44 reported trends of secondary preventive therapies using the National Health and Nutrition Examination Survey and found a 21% rate of ACEI use. This substantial difference may be due in part to our inclusion of a higher-risk group of CLI patients who often present with more severe PAD symptoms and comorbidities, such as diabetes and HTN.…”
Section: Discussionmentioning
confidence: 99%
“…21 A number of observational and single center studies have shown that patients with PAD and CLI are under-treated with guideline-recommended therapies (anti-platelet therapy, statins, and antihypertensive therapies). 22 Furthermore, under-treatment with guideline-recommended therapies was associated with increased repeat revascularization and amputation in patients undergoing revascularization. 23…”
Section: Critical Limb Ischemiamentioning
confidence: 99%
“…21 A number of observational and single center studies have shown that patients with PAD and CLI are under-treated with guideline-recommended therapies (anti-platelet therapy, statins, and antihypertensive therapies). 22 Furthermore, under-treatment with guideline-recommended therapies was associated with increased repeat revascularization and amputation in patients undergoing revascularization. 23 The role of supervised exercise training is limited in patients with CLI, given the extent of disease, associated ulcers or gangrene, and the fact that arterial perfusion is inadequate for basal metabolic requirements and not sufficient to improve the metabolic efficiency of exercising muscles.…”
Section: Critical Limb Ischemiamentioning
confidence: 99%